2021
DOI: 10.3390/jcm10235598
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anesthetic Techniques on the Risk of Postoperative Complications Following Lower Extremity Amputation in Diabetes Patients with Coagulation Abnormalities: A Retrospective Cohort Study Using Propensity Score Analysis

Abstract: Diabetic foot amputation is associated with high morbidity and mortality rates. To prevent cardiovascular complications along with vasculopathy in the course of diabetes mellitus, a high number of patients receive anticoagulant therapy. However, anticoagulants are contraindicated in neuraxial anesthesia limiting available anesthetic modalities. Therefore, in this retrospective study, we aimed to compare between general anesthesia and peripheral nerve block (PNB) with respect to postoperative complications foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Hou Yee Lai 29 found that peripheral nerve block provided more stable hemodynamics for patients undergoing unilateral diabetic foot surgery below the knee compared to lumbar anesthesia. Hye Jin Kim 30 reviewed 320 patients with diabetes treated with lower limb amputation under nerve block anesthesia or general anesthesia and found that the general anesthesia group had a higher crystal infusion volume and a higher frequency of vasopressors, especially norepinephrine. This is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Hou Yee Lai 29 found that peripheral nerve block provided more stable hemodynamics for patients undergoing unilateral diabetic foot surgery below the knee compared to lumbar anesthesia. Hye Jin Kim 30 reviewed 320 patients with diabetes treated with lower limb amputation under nerve block anesthesia or general anesthesia and found that the general anesthesia group had a higher crystal infusion volume and a higher frequency of vasopressors, especially norepinephrine. This is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%